The chemical composition of the secretions, their antibacterial activity, and the pygidial gland morphology of selected European Carabini ground beetles (Coleoptera: Carabidae) - Nikola Vesović; Marija Nenadić; Sofija Vranić; Ljubodrag Vujisić; Katarina M. Milinčić; Marina Todosijević; Ivica Dimkić; Tamara Janakiev; Nina B. Ćurčić; Nataša Stevanović; Ljiljana Mihajlović; Danijela Ž. Vukoičić; et al. (Frontiers in Ecology and Evolution, 2023)
The pygidial glands of carabids produce strong-smelling vapours. In this study, we examined the chemical composition of the gland secretions and the structure of the glands in five species of Carabini ground beetles (one species from the subtribe Calosomatina and four species from the subtribe Carabina): Calosoma (Calosoma) maderae (Fabricius, 1775), Carabus (Carabus) granulatus Linnaeus, 1758, C. (Limnocarabus) clathratus Linnaeus, 1760, C. (Carabus) ulrichii Germar, 1823, and C. (Procerus) gigas Creutzer, 1799. Additionally, we tested the antibacterial potential of the pygidial gland secretions of the two latter species against 11 bacterial strains. In order to detect the chemical content of the secretions, we used gas chromatography–mass spectrometry (GC–MS). The secretion extracts were applied against selected strains of medically important bacteria. We used bright-field microscopy to examine the morphology of the glands. We discovered a total of 11 chemical compounds in the pygidial gland extracts of the ground beetles we analysed. Ten of these compounds were identified as seven carboxylic acids, two hydrocarbons, and one aromatic aldehyde, while one chemical remained unidentified. Most of the components were isolated from the secretion of C. (L.) clathratus (nine), while the lowest number of compounds was found in C. (P.) gigas (two). Methacrylic acid was the most dominant compound by percentage in all five species, while angelic acid was also detected in all samples. As expected, salicylaldehyde was exclusively found in the species of the genus Calosoma Weber, 1801. The secretion of C. (P.) gigas was shown to achieve the highest level of antibacterial activity against Pseudomonas aeruginosa, Salmonella enterica, and S. typhimurium (even the same level as the positive control streptomycin), while the secretion of C. (C.) ulrichii achieved the highest antimicrobial potential against Staphylococcus epidermidis, S. aureus, Listeria monocytogenes, and Bacillus cereus. The most noticeable difference in the structure of the glands between the two genera is that the reservoir in Calosoma is more significantly narrowed as it leads into the efferent duct, compared to that of Carabus.